Importance of Uncertainties in the Spatial Distribution of Preindustrial Wildfires for Estimating Aerosol Radiative Forcing - J. S. Wan; D. S. Hamilton; N. M. Mahowald (Geophysical Research Letters)
Abstract Uncertainty in preindustrial aerosol emissions, including fires, is one of the largest sources of uncertainty in estimating anthropogenic radiative forcing. Here, we quantify the range in aerosol forcing associated with uncertainty in the location and magnitude of preindustrial fire emissions in a climate model based on four emission estimates. With varied emission location and magnitude among the fire estimates, we find the change in aerosol forcing from present‐day to preindustrial is between −0.4 and 0.3 W/m2 for direct radiative forcing and between −1.8 and 0.6 W/m2 for cloud albedo forcing. Altering only the spatial distribution of preindustrial fires for a fixed magnitude adds a previously unaccounted 25% uncertainty to the total aerosol radiative forcing range. Future studies must account for the uncertainty in the spatial distribution of fire and other aerosol emissions as regional differences contribute substantial additional uncertainty to anthropogenic radiative forcing estimates and the resultant climate sensitivity.